Grievance Redress Mechanisms in the Public Sector: A Literature Review - Pande, Suchi; Hossain, Naomi (Open Government Partnership and Accountability Research Center, 2022)
Grievance redress mechanisms (GRMs) in the public sector are institutionalized processes designed to enable people to complain about and seek redress for services they rightfully should have received. This paper reviews evidence on GRMs from around the world, focusing on mechanisms attached to public services and programs in the Global South, where they are relatively new and emerging fast. GRMs matter in particular in the Global South because they are increasingly widespread and found in multilateral aid programs, across national governments, within specific programs and services, as well as in the private sector. GRMs are expected to improve public service efficiency, effectiveness, and fairness by giving people a systematic means of seeking redress for governance failures, and they have strong potential to improve accountability to the most excluded and marginalized people, who tend to find it most difficult to make claims on their state. The review includes a simple framework for understanding the key elements of successful GRMs, as identified through the review process. These are: • Citizen capacity to complain • State capacity to respond • Proactive transparency The review concludes with key research questions to improve our understanding of how GRMs work and could be better designed and implemented.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; governance / governação; mecanismos de reclamação / grievance redress mechanisms; ⛔ No DOI found

What actually is social accountability? - Aston, Thomas (Medium, 2021)
Figuring out “what is the work?” we actually do sounds like a simple task, but in fact, it’s surprisingly difficult.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Accountability Ecosystems: The Evolution of a Keyword - Halloran, Brendan (Accountability Research Center, 2021)
Efforts to strengthen the accountability of the governing to the governed go back millennia. However, in the past decade there has been a renewed debate about how to advance public accountability. One domain where this conversation has taken place is that of efforts funded by donors (government development agencies and private philanthropies), primarily in the Global South and implemented by a set of national and international actors, including NGOs, private sector project implementors, and international institutions. Unfortunately, much donor-funded work has been underpinned by an understanding of accountability grounded in optimistic assumptions, particularly around the role of transparency and information technology. Early efforts by Rosie McGee and John Gaventa to take stock of this work highlighted the lack of theories of change grounded in a more nuanced, holistic and politically-informed understanding of accountability. Others began questioning the dominant ‘transparency + participation = accountability’ formulation that underpinned many projects; and most of them were just that, projects: start date, end date, work plan, logical framework, funding proposal, budget, etc. It was at the beginning of this discussion about what it takes to achieve real accountability that the term ‘Accountability Ecosystem’ started being used by a few individuals and organizations. The organization I worked for at the time, the Transparency and Accountability Initiative (TAI), had picked up the term, potentially from the organization I work for now, the International Budget Partnership (IBP).[i] I saw the term as a way to advance a more holistic and dynamic way to talk about the interaction of accountability actors, mechanisms and efforts in a given context, and a deliberate step away from more simplistic, linear formulations.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Citizen engagement in public services in low- and middle-income countries: A mixed-methods systematic review of participation, inclusion, transparency and accountability (PITA) initiatives - Waddington, Hugh; Sonnenfeld, Ada; Finetti, Juliette; Gaarder, Marie; John, Denny; Stevenson, Jennifer (Campbell Systematic Reviews, 2019)
Background How do governance interventions that engage citizens in public service delivery planning, management and oversight impact the quality of and access to services and citizens’ quality of life? This systematic review examined high quality evidence from 35 citizen engagement programmes in low- and middle-income countries that promote the engagement of citizens in service delivery through four routes: participation (participatory priority setting); inclusion of marginalised groups; transparency (information on rights and public service performance), and/or citizen efforts to ensure public service accountability (citizen feedback and monitoring); collectively, PITA mechanisms. We collected quantitative and qualitative data from the included studies and used statistical meta-analysis and realist-informed framework synthesis to analyse the findings. Results The findings suggest that interventions promoting citizen engagement by improving direct engagement between service users and service providers, are often effective in stimulating active citizen engagement in service delivery and realising improvements in access to services and quality of service provision, particularly for services that involve direct interaction between citizens and providers. However, in the absence of complementary interventions to address bottlenecks around service provider supply chains and service use, citizen engagement interventions alone may not improve key wellbeing outcomes for target communities or state-society relations. In addition, interventions promoting citizen engagement by increasing citizen pressures on politicians to hold providers to account, are not usually able to influence service delivery. Conclusions The citizen engagement interventions studied were more likely to be successful: (1) where the programme targeted a service that citizens access directly from front-line staff, such as healthcare, as opposed to services accessed independently of service provider staff, such as roads; (2) where implementers were able to generate active support and buy-in for the intervention from both citizens and front-line public service staff and officials; and (3) where the implementation approach drew on and/or stimulated local capacity for collective action. From a research perspective, the review found few studies that investigated the impact of these interventions on women or other vulnerable groups within communities, and that rigorous impact evaluations often lack adequately transparent reporting, particularly of information on what interventions actually did and how conditions compared to those in comparison communities.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Theories of Change for Promoting Empowerment and Accountability in Fragile and Conflict-Affected Settings - Green, Duncan (IDS, 2017)
This paper explores the current state of thinking among a range of aid actors (multilaterals, bilateral, applied scholars and international non-governmental organisations) on how to promote empowerment and accountability in fragile, conflict and violence affected settings. It seeks to identify trends, gaps and weaknesses in that thinking, and propose research questions and hypotheses to test. Three underlying sources of confusion are identified that are hindering progress on both understanding empowerment and accountability in fragile, conflict and violence affected settings, and taking helpful action to promote it. They are: (1) theory of endogenous change (e.g. on how empowerment and accountability arise in situ) versus the theory of action of an external intervention; (2) fragility versus conflict: there is no clear justification for combining these different aspects into a single category; and (3) empowerment versus accountability: donor analysis and practice has been overwhelmingly weighted towards accountability, exhibiting limited understanding or interest in the nature of power.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; conflict / conflito; empowerment / empoderamento; fragility / fragilidade

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Social Accountability: What Does the Evidence Really Say? - Fox, Jonathan A. (World Development, 2015)
Empirical evidence of tangible impacts of social accountability initiatives is mixed. This meta-analysis reinterprets evaluations through a new lens: the distinction between tactical and strategic approaches to the promotion of citizen voice to contribute to improved public sector performance. Field experiments study bounded, tactical interventions based on optimistic assumptions about the power of information alone, both to motivate collective action and to influence the state. Enabling environments for collective action combined with bolstered state capacity to respond to citizen voice are more promising. Sandwich strategies can help ‘voice’ and ‘teeth’ to become mutually empowering, through state–society synergy.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; transparency / transparência

Abordagens para promover responsabilização social: revisão de algumas experiências - McGee, Rosie; Wanjiku Kelbert, Alexandra (Laboratório de Inovação do CEP - CEP - Cidadania e Participação, 2014)
O Programa Cidadania e Participação (CEP) (2013-2018) apoia os cidadãos na monitoria da qualidade de prestação de serviços de saúde e de educação em quatro províncias de Moçambique, assim como a advogar para a melhoria da qualidade desses serviços nos níveis distrital, provincial e nacional. O CEP pretende contribuir para: uma maior disponibilidade de informação relevante de modo a que os cidadãos tenham um melhor acesso e benefício dos serviços prestados pelo sector público; melhorar as capacidades dos cidadãos de avaliar a prestação de serviços e de se envolverem com os provedores de serviços de modo a melhorar a qualidade dos serviços de saúde e educação aos níveis primário e secundário; apoiar as organizações da sociedade civil a impulsionarem essas constatações nos processos de tomada de decisões a níveis mais altos.Este programa facilitará o diálogo entre cidadãos e comunidade por um lado, e os provedores de serviços por outro lado, para melhorar a qualidade dos serviços. Esta análise constitui uma parte da contribuição do IDS para o Output 5 do CEP (Output 5: ‘Aprendizagem e metodologias compartilhadas e aplicadas por outros actores do desenvolvimento’). Esta fornece uma visão geral de algumas das mais inovadoras experiências de responsabilização social e práticas de envolvimento dos cidadãos de vários contextos africanos, bem como internacionais, como forma de ajudar a aumentar o nível geral de interesse e consciencialização sobre práticas inovadoras de envolvimento dos cidadãos em Moçambique.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação

The Effects of Sector Characteristics on Accountability Relationships in Service Delivery - Mcloughlin, Claire; Batley, Richard (Social Science Research Network, 2012)
Why do different services encounter particular constraints and opportunities in their delivery? This working paper identifies a set of characteristics that can be used to differentiate between services, and between functions within them, and asks how these defining or ‘fixed’ characteristics may influence key relationships of accountability and control.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil

Concept Paper on Decentralisation and Local Governance. Module 1: definitions and concepts. - Olsen, Hans Bjørn (Concept paper, 2007)
SDC has been implementing projects in support to decentralisation and local governance for about 15 years. Today, arounf 2/3 of SDC's country programmes include a support to local governance and/or decentralisation. For this reason, an independent evaluation of  SDC’s achievements on “Decentralisation  and local governance” took place in 2006‐2007. One of the recommendations of this evaluation  was to  carry out  a capitalisation of SDC’s experiences in this field. SDC’s  Governance  Division has been charged with implementing this recommendation and  has planned a two‐step process: first to clarify concepts; and secondly, to identify SDC’s practical lessons learnt in this field.  The present document has 3 main objectives: ‐To further a common understanding about concepts linked to decentralisation and local governance  within SDC (HQs and field). ‐ To give basic conceptual elements for capacity building activities in decentralisation ‐ The document does not pretend to be an academically precise paper, but rather a short and succinct  presentation of the various concepts. Therefore, this document does  not  present  a collection of practical experiences from SDCs many  interventions in developing countries, but is the 1st  module of a series of two documents. The 2nd  module  will be published  at the  end of 2008 and will include  practical and concrete recommendations and tips,  which will compiled at the capitalisation workshop of SDC’s experiences in supporting decentralisation  and local governance processes (planned for June 2008).
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; decentralization / descentralização; governance / governação

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde

All hands on deck: Harnessing accountability through external public audits | Publications (International Budget Partnership)
This report is the first ever comprehensive look at the strength of audit and oversight systems globally and comes at a time when supreme audit institutions (SAIs) are under enormous pressure to ensure governments are effective stewards of COVID-19 emergency spending in ways that advance the public interest and protect development progress.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Citizen Participation in Auditing in Latin America: The Future Agenda - Marcos Mendiburu (Accountability Research Center and Controla Tu Gobierno)
A group of civil organizations committed to strengthening state-society synergies for accountability and Mexico’s National Audit Office (ASF) jointly organized the International Seminar on Citizen Participation and External Auditing in September 2020. More than five thousand people from 21 countries registered, and there were more than eighteen thousand virtual participants throughout the three days of the event.[1] During the seminar, participants shared an assessment on the state of the subject regionally, research on the progress made at the sub-national level in a couple of countries, SAIs practices in the region, and examples from civil society on the use of SAI-generated information. Not only was the seminar useful to discuss progress and existing gaps but also to develop a series of proposals and recommendations that could be followed by OLACEFS and the SAIs themselves to expand on this issue. Seminar participants acknowledged that citizen participation has advanced faster than its implementation by most SAIs in the region, which usually encompasses limited participation exercises. Thus, there is a risk that promoting citizen participation may constitute an effort to “be compliant” but not to generate any relevant impact on auditing. Among the factors that would explain this situation were: the false dilemma between “citizen participation” and “audit”—based on the assumption that the former could affect the independence of the SAIs and/or the objectivity of the auditing; the organizational culture of the SAIs themselves; and the limitations of the citizen reporting mechanism as the dominant practice for citizen participation. The ‘minimalist approach’ to citizen participation in auditing adopted by many of the region’s SAIs entails the need to go beyond their comfort zone and seriously consider the results and the impact of citizen participation, its sup-porting evidence, and how achievements are measured. In other words, citizen participation in audits must be results-oriented. Therefore, rigorous metrics are required on SAIs’ efforts to promote citizen participation. The data related to the implementation and results of citizen participation in audits by SAIs should be publicly disclosed on their institutional websites. At the seminar, some institutionalized practices on citizen participation in auditing were shared, such as the participatory planning of the SAI from Argentina, the Council of Civil Society Associations (COSOC) of the SAI from Chile, the articulated audit of the SAI from Colombia, and the citizen report mechanism of the SAI from Mexico. However, the engagement of indigenous communities in the audit on the quality of drinking water services con-ducted by the Costa Rican SAI in 2018 showed that an enabling legal framework or specific internal regulations are not always required for SAIs to promote citizen participation. In this case, there was no internal practice to support such participation, but the willingness to experiment was essential. The innovation in SAIs must go hand in hand with citizen participation. This experience also highlighted the importance of involving the ultimate beneficiaries of the audit: the community members themselves. It was emphasized that a broader view of citizen participation in SAIs requires an analysis of the various profiles of potential civil society participants. It also requires an understanding of the mechanisms these participants use to participate, their motivations, their possible contributions to an effective participation in an audit, and an adjustment of the practices implemented when they encounter obstacles gaining access to them. This approach also calls for adopting citizen participation practices based on a collaborative approach between citizens and SAIs instead of adopting consultative-nature practices prevalent in most institutions. This implies that citizen participation practices must be jointly created, that is, created from and with the citizens, not for the citizens. Furthermore, this approach involves citizen participation throughout the audit cycle, including during the execution and/or follow-up phase of an audit, when feasible and appropriate. Likewise, it is also necessary to promote the accountability of citizen contributions or inputs from start to end, including the actions implemented by the SAIs (reporting on their capacity to respond or ‘responsiveness’) and how these actions or responses have contributed to other actions or changes by third parties. This requires SAIs to take a different perspective when reporting their achievements to transcend audit reports (and their findings or recommendations), emphasizing their contribution to the accountability ecosystem (for example, how other oversight bodies, the media, and society have used audit products), and how this contributes to improving people’s lives. This is key to prove the added value of SAIs in today’s world. In summary, the challenges of the 21st century require public institutions to collaborate with other stakeholders, focus on results, be innovative, and use knowledge to adapt to changes in the external environment.[2] These characteristics or qualities also need to be present among SAIs. Notes [1] The seminar was broadcast on YouTube. Please note that only those who wished to obtain a certificate of attendance registered, although others connected to the live broadcast without prior registration. On the other hand, the total number of virtual participants comprises the total number of people connected in each of the sessions. [2] These qualities were pointed out by Diego Arisi, the IDB’s leading state modernization specialist, on November 20 at an event held in Bogotá, Colombia.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; civil society / sociedade civil